Cd22 controls germinal center b cell receptor signaling, which influences plasma cell and memory b cell output - Meyer, Sarah Johanna; Steffensen, Marie; Acs, Andreas; Weisenburger, Thomas; Wadewitz, Charlotte; Winkler, Thomas; Nitschke, Lars (Journal of Immunology, 2021)
Germinal center reactions are established during a thymus-dependent immune response. Germinal center (GC) B cells are rapidly proliferating and undergo somatic hypermutation in Ab genes. This results in the production of high-affinity Abs and establishment of long-lived memory cells. GC B cells show lower BCR-induced signaling when compared with naive B cells, but the functional relevance is not clear. CD22 is a member of the Siglec family and functions as an inhibitory coreceptor on B cells. Interestingly, GC B cells downregulate sialic acid forms that serve as high-affinity ligands for CD22, indicating a role for CD22 ligand binding during GC responses. We studied the role of CD22 in the GC with mixed bone marrow chimeric mice and found a disadvantage of CD222/2 GC B cells during the GC reaction. Mechanistic investigations ruled out defects in dark zone/light zone distribution and affinity maturation. Rather, an increased rate of apoptosis in CD222/2 GC B cells was responsible for the disadvantage, also leading to a lower GC output in plasma cells and memory B cells. CD222/2 GC B cells showed a clearly increased calcium response upon BCR stimulation, which was almost absent in wild-type GC B cells. We conclude that the differential expression of the low-affinity cis CD22 ligands in the GC normally results in a strong attenuation of BCR signaling in GC B cells, probably due to higher CD22-BCR interactions. Therefore, attenuation of BCR signaling by CD22 is involved in GC output and B cell fate.
CRIS-Team Scopus Importer:2021-08-20